Organizational Culture Mediates the Relationship Between Transformational Leadership and Work Outcomes - Burton, Laura J.; Peachey, Jon Welty (Journal of Intercollegiate Sport, 2014)
The objectives of this study were to examine the mediating effect of group and developmental organizational culture types on the relationship between transformational leadership and three outcome variables—affective organizational commitment, turnover intentions, and job search behaviors. Senior administrators (n = 188) working in NCAA Division I intercollegiate athletic departments completed a survey assessing perceptions of leadership behavior of their athletic directors, the culture of their athletic departments, and their affective organizational commitment, turnover intentions, and job search behaviors. Results indicate that group culture partially mediates the relationship between transformational leadership and affective organizational commitment, and fully mediates turnover intentions and job search behaviors. Developmental culture partially mediates affective organizational commitment but has no influence on turnover intentions and job search behaviors. Findings contribute to the understanding of the important mediating role of organizational culture on the relationship between transformational leadership and outcome variables in the intercollegiate athletics context.